Could echocardiographic left atrial characterization have additive value for detecting risks of atrial arrhythmias and stroke in patients with hypertrophic cardiomyopathy?. (3rd October 2022) - Al Wazzan, A; Galli, E; Lacout, M; Paven, E; L'official, G; Schnell, F; Oger, E; Donal, E
Abstract: Background: Atrial arrhythmia (AA) is considered a turning point for prognosis in hypertrophic cardiomyopathy (HCM) patients. Prediction of AA and associated stroke risk in patients with HCM is an important clinical challenge as these events can occur in young subjects and significantly impact their quality of life. (1) (2) Purpose: We sought to assess whether an echocardiographic evaluation focused on the left atrial (LA) characterization could estimate the occurrence of AA and stroke in HCM patients. Methods: 216 HCM-patients (52±16 years old) were enrolled between 2016 and 2019. All patients underwent transthoracic echocardiography for the evaluation of left atrial volume (LAV), left ventricular global longitudinal strain (LV-GLS), peak left atrial strain (PLAS) and peak atrial contraction strain (PACS) by speckle-tracking imaging. A composite endpoint was defined as a history of AA and/or a history of stroke or peripheral embolism and/or occurrence of AA. Results: The patients were followed for 2.9 years. Among the 216 patients, 78 (36%) met the composite endpoint. These patients were older (50.3±16.7 vs. 57.1±14.4 years, p=0.0035), had a higher prevalence of arterial hypertension (42.3% vs. 62.3%; p=0.005) and had higher NT-proBNP levels. LAV (37.2±15.7 vs. 47±20 ml/m 2, p=0.0001) was significantly higher in patients who met the composite endpoint, whereas PLAS and PACS were significantly impaired (26.6±9.12 vs. 19.3±9.54%; p<0.0001 and 13.1±6.3% vs. 8.8±6.5%; p<0.0001, respectively). After adjustment, PLAS and PACS remained independently associated with events with an odds ratio (OR) of 0.42 for PLAS (95% CI, [0.29–0.61]; p<0.0001). Stroke occurred in 67% of the patients without any clinical AA. PLAS with a cut-off of under 15.5% provided event detection with 91% specificity and demonstrated a predictive value for new-onset of AA. Although there was a high correlation between PLAS and LV-GLS, LV-GLS was not associated with the events. Conclusion: The impairment of LA function assessed by 2D speckle-tracking echocardiography was strongly associated with AA and the risk of stroke, even in patients without any documented AA. Its value for guiding the management of HCM-patients requires further investigation. Funding Acknowledgement: Type of funding sources: None.